Difference between Okinawan and Dutch older adults in prefrontal brain activation - Ćurčić-Blake, Branislava; Futenma, Yuko; Willcox, Donald Craig; Tazangi, Parisa Esmaeili; Wardana, Nido Dipo; Ueda, Yukihiko; Aleman, André (Frontiers in Aging Neuroscience, 2025)
BackgroundOlder adults in Okinawa (Japan) are known for healthy aging and longevity. This is the first study to explore brain activation during executive functioning in Okinawan older adults in comparison to Western-European (Dutch) older adults.MethodsA total number of 80 participants were included in the study (41 from the Netherlands and 39 from Okinawa), with ages between 65 and 80 years). The groups did not differ for sex and handedness. Brain activation was measured during a visual working memory task and a verbal fluency task, for bilateral frontal cortex using functional near infrared spectroscopy (fNIRS). We investigated oxygenated hemoglobin (HbO) levels and laterality index.ResultsBoth groups performed within the normal range for their population. During verbal fluency, less activation in the left frontal gyrus was observed in Okinawa participants as compared to Dutch participants, and more activation in the anterior superior parts of the frontal gyrus. For the n-back task, the Okinawa group exhibited less activation in the right dorsolateral prefrontal cortex and more activation in the bilateral anterior frontal gyrus. Although laterality indices were similar for both tasks, Okinawa participants showed stronger left lateralization during category fluency.ConclusionOur results reveal less activation of the task-relevant areas in participants from Okinawa as compared to Dutch participants. It could be hypothesized, with caution, that Okinawan older adults may need less executive processing resources to perform the task. Other differences in activation may be related to different strategy use, which may be studied in more detail in future investigations.